Вязаные мишки с описаниями и шаблонами: [6+] / Г. П. Панина - Панина Галина Петровна (Азбука рукоделия, 2014)
Экземпляры: ф.14 (20140516) / Инвентарный номер: 50402 / Цена: 162. 00.р. / Сис.шифр: 37. 248 / Авт.знак: П 16 / ББК: 37.248